Effects of habitat structure on the mollusc assemblage in Mussismilia corals: evaluation of the influence of different coral growth morphology. (8th February 2021) - Nogueira, M. M.; Neves, E.; Johnsson, R.
Abstract: Habitat structure increases richness and abundance of species in many environments by providing easy access to resources and refuge from predators. In coral reefs, corals are habitat for many organisms and differences in their morphologies may act as variation in habitat structure for associated fauna. In the present study, we investigate whether there are differences in the richness and abundance of molluscs associated with three species of Mussismilia corals exhibiting different growth morphologies, in two different reef areas of the Bahia state. Mussismilia harttii has a meandroid pattern, M. hispida is a massive coral, M. braziliensis also has a massive growth pattern with crevices at the corallum base. Coral characteristics were measured in the laboratory. Significant differences were identified for richness among coral species – higher values were reported in colonies of M. harttii and no significant statistical differences were observed between M. braziliensis and M. hispida . Considering the density of associated molluscs, the same pattern was found. The results are in accordance with previous studies and indicate the importance of M. harttii as a key habitat to maintain a richer and more abundant associated fauna. The internal volume of interpolypal space is an important factor influencing the richness and density of associated species.